2007
DOI: 10.1111/j.1439-0272.2007.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin correlates in infertile oligozoospermic males

Abstract: Leptin is an adipocyte-secreted protein that participates in the regulation of energy homeostasis. Eighty men were investigated; fertile normozoospermia as a control (n = 30) and infertile oligozoospermia (n = 50). The patients underwent estimation of body weight (kg), height (cm), calculation of body mass index (BMI), semen analysis, serum leptin and testosterone hormones. Mean body weight was significantly higher in infertile oligozoospermia compared with controls. Mean height, BMI and serum testosterone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
3
11
0
1
Order By: Relevance
“…Raised serum leptin is also associated with sperm function changes in males [35,36]. The serum ranges of leptin in this study generally agree with concentrations found in healthy, obese and infertile male cohorts reported in the literature [35-38]. …”
Section: Discussionsupporting
confidence: 89%
“…Raised serum leptin is also associated with sperm function changes in males [35,36]. The serum ranges of leptin in this study generally agree with concentrations found in healthy, obese and infertile male cohorts reported in the literature [35-38]. …”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the BMI was positively correlated with serum LH and leptin levels. Several reports showed that the accumulation of fatty tissue in men was associated with decreased total, free T, and increased E 2 serum levels (17,18). Zohdy et al (19) reported significant negative correlation between BMI and serum total T. Zorn et al (20) demonstrated a link between leptin and testicular function, independent of FSH and LH, possibly involving T and SHBG through a regulation of Leydig cell function.…”
Section: Discussionmentioning
confidence: 96%
“…In another study, Hanafy et al (17) divided 80 men presenting at an andrology clinic for evaluation of infertility in their marriage into two groups (fertile normozoospermic and infertile oligospermic) based on their reproductive history and semen analysis. Body weight was higher (84.6 AE 16.3 kg) in the infertile group than in the fertile group (76.6 AE 12.5 kg) (P<.05), but BMI in the infertile group was only slightly higher and not statistically significantly different from that of the fertile group.…”
Section: Evidence From Studies Of Couples Seeking Fertility Treatmentmentioning
confidence: 99%